Studi Deskriptif Eksploratif Kejadian IUFD - Septerina P W; Puji Hastuti; Rusmini Rusmini (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The purpose of this study was to describe the incidence of IUFD in hospitals Goeteng Purbalingga. This research is a descriptive study. The population of all women giving birth with IUFD from January through August 2014. Samples were some 26 people. The sampling technique with a total sampling. The characteristics of mothers were based on age 76.9% is not at risk , based on parity 53,8% multiparous. The causes of women giving birth with IUFDwere 38 ,5% are maternal factors, 46,2% are of fetal factors, 30,8% are placental factors. 50 % of maternal were caused by infection, 33,3% due to infection, and 75% due to placental abnormalities of the umbilical cord. It is suggested for Hospital to provide health education about the signs and symptom of danger in pregnancy.